Results of experimental study to investigate the effect of fertilizers with enzyme-active strains of microorganisms in biological rehabilitation of mining projects in Gobi region of Mongolia (Mongolian Journal of Agricultural Sciences, 2014)
Mining extraction operations of bigger mining projects in the Gobi region are causing significant environmental pollution including soil erosion and degradation in the surrounding areas of the mine sites. Therefore, there is a crucial need for soil rehabilitation and re-vegetation of native/aboriginal plants when efforts are made to rehabilitate mines and restore them to comparable natural pristine conditions. DOI: http://dx.doi.org/10.5564/mjas.v11i2.222 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.77-78